Redesign Rural Tourism Product Based Digital Nomadism Postpandemic COVID-19 in Bali - Situmorang, Fransisco; Erwin Trisnajaya Karthana (Politeknik Pariwisata NHI Bandung, 2021)
This study analyzes efforts to redesign and develop rural tourism products based on digital nomadism in the Tegalmengkeb Village post-COVID-19 pandemic. Data obtained through observation, documentation, and interviews with twelve informants selected using purposive sampling. Data were analyzed using a qualitative approach. This study indicates that rural tourism products-based digital nomadism is feasible to develop in Tegalmengkeb Village, especially Banjar Kelecung Kelod, by providing an adequate internet connection and constructing co-spaces. This study contributes to policy recommendations for tourism development in Tegalmengkeb Village and enriches literature regarding the outcome of digital nomadism destinations in rural areas still very minimal among academics